EFFECTIVENESS OF STRUCTURED TEACHING MODULE ON KNOWLEDGE REGARDING REVISED NATIONAL TUBERCULOSIS CONTROL PROGRAM AMONG FINAL YEAR B.SC NURSING STUDENTS OF SELECTED NURSING COLLEGES AT BANGALORE - PROF. PERIADURACHI KUMAR; DR. K.R.JOHN (International Journal of Pharma and Bio Sciences, 2015)
Tuberculosis is a major public health problem that has been traumatizing human race for centuries. This study was aimed at determining the level of knowledge regarding RNTCP among the final year B.Sc Nursing students and the effect of a structured teaching programme in improving their knowledge. One group pretest-posttest design was adopted for the study and a sample size of 300 final year B.Sc Nursing students drawn randomly from 6 colleges. The data obtained was analyzed using descriptive and inferential statistical methods and interpreted in relation to the objectives of the study. The level of significance was set at 0.05. It was found that, the knowledge of RNTCP among the subjects was inadequate in the greater majority of the respondents. The teaching programme was found to be effective in improving knowledge on RNTCP among the subjects with t-value of 1.647. Knowledge level among the subjects on RNTCP was inadequate and paired "t" test indicated at p=0.05 that, teaching on revised national tuberculosis control program was effective in increasing the knowledge level of final year B.Sc. Nursing students